2000
DOI: 10.1152/ajplung.2000.279.6.l1146
|View full text |Cite
|
Sign up to set email alerts
|

KGF regulates pulmonary epithelial proliferation and surfactant protein gene expression in adult rat lung

Abstract: Keratinocyte growth factor (KGF, FGF-7) is a potent mitogen for epithelial cells. We instilled recombinant human KGF to determine the effects of KGF on alveolar epithelial cells. Left lungs of adult rats were instilled intrabronchially with KGF (5 mg/kg) or normal saline. KGF instillation resulted in epithelial cell hyperplasia, and the alveolar bromodeoxyuridine (BrdU) labeling index peaked at 35% on day 2 after instillation. The mRNA levels for the surfactant proteins (SPs) SP-A, SP-B, and SP-D were increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
99
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 40 publications
7
99
0
Order By: Relevance
“…Total cellular RNA was isolated by ultracentrifugation for 18 h at 150,000 g through a 5.7 M CsCl cushion. Total RNA isolated from type II cells was analyzed for surfactant protein mRNA expression with a ribonuclease protection assay (RPA) that allowed simultaneous measurement of mRNAs for SP-A, -B, -C, and -D as described previously (46,54). The primers used to generate the riboprobes and their sizes have been reported (54).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total cellular RNA was isolated by ultracentrifugation for 18 h at 150,000 g through a 5.7 M CsCl cushion. Total RNA isolated from type II cells was analyzed for surfactant protein mRNA expression with a ribonuclease protection assay (RPA) that allowed simultaneous measurement of mRNAs for SP-A, -B, -C, and -D as described previously (46,54). The primers used to generate the riboprobes and their sizes have been reported (54).…”
Section: Methodsmentioning
confidence: 99%
“…Keratinocyte growth factor (KGF), fibroblast growth factor (FGF)-7, and acidic FGF (FGF-1) increase expression of surfactant proteins A, B, and D (SP-A, SP-B, and SP-D, respectively) (46,48,52). Both SP-A and SP-D are increased in lavage fluid of rats instilled with KGF (54). Corticosteroids are especially stimulatory for the expression of SP-B but may be inhibitory for SP-A and SP-C (2,46).…”
mentioning
confidence: 99%
“…8). Growth factor signaling is an essential component of the regulatory network controlling proliferation, differentiation and pattern formation of the lung (Cardoso et al, 1997;Yano et al, 2000;Mason et al, 2003;Portnoy et al, 2004). As TGF␤2 signaling is known to inhibit lung maturation and type II cell differentiation (Whitsett et al, 1992;Lebeche et al, 1999), effects of Cebpa deletion may be mediated in part by increased expression of TGF␤2.…”
Section: Research Article C/ebp␣ Is Required For Lung Maturationmentioning
confidence: 99%
“…We found that SU5402 treatment down-regulated 136 epithelial genes (Table 1). These included genes that have been previously described to be FGF-sensitive, such as Sftpa, Sftpb, and Sftpc (Cardoso et al, 1997;Matsui et al, 1999;Tichelaar et al, 2000;Yano et al, 2000;Clark et al, 2001;Hyatt et al, 2004). Of the 136 genes decreased in SU5402-treated epithelium, there were five transcription factors (Hnf4a, Atoh1, Nkx3-1, Trp63, and Elf5).…”
Section: Su5402 Treatment Decreases Expression Of Fgfresponsive Genesmentioning
confidence: 99%